A Review of the Measures to Enhance Power Systems Resilience - Mahzarnia, Maedeh; Moghaddam, Mohsen Parsa; Baboli, Payam Teimourzadeh; Siano, Pierluigi (IEEE systems journal, 2020)
Rare and extreme climate events may result in wide power outages or blackouts. The concept of power system resilience has been introduced for focusing on high-impact and low-probability (HILP) events such as a hurricane, heavy snow, and floods. Power system resilience is the ability of a system to reduce the likelihood of blackout or wide power outages due to HILP events. Indeed, in a resilient power system, as the severity of HILP events increases, the rate (but not the amount) of unserved loads diminishes. Suitable measures for managing power system resilience can be classified into three categories in terms of time, known as "resilience-based planning," "resilience-based response," and "resilience-based restoration." The most widely used approaches, methods, and techniques in each of these categories, as well as the future trends for improving the power system resilience are reviewed in this article. The challenges of resilience in power systems with high penetration of renewable energy sources are also discussed in each of these categories.